PENGARUH KUALITAS PELAYANAN DAN CITRA KORPORASI TERHADAP KESETIAAN PELANGGAN MELALUI KEPUASAN PELANGGAN - Fransisca Sandra Christina (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this research is Customer loyalty as a competitive advantage in serviceindustry. The objective of this research is to examine the impact of Service quality, Corporateimage on Customer loyalty through Customer satisfaction. The design of this research appliesprimary data obtained by distributing questionnaires to 200 patients of Womens’s and Children’sHospital in Jakarta. Data analysis method used in this research is Structural Equation Model(SEM). The result of this research concludes that there is positive impact Interaction quality,Peer-to-peer quality, Corporate image toward Customer satisfaction, and there is positive impactInteraction quality, Peer-to-peer quality, Corporate image, Customer satisfaction towardCustomer loyalty. Meanwhile, there is no positive impact Outcome quality towards Customersatisfaction and Customer loyalty.Keywords: Service quality, Outcome quality, Interaction quality, Peer-to-peer quality, Corporateimage, Customer satisfaction, Customer loyalty